PUBLIC ADMINISTRATION OF LAND MARKET IN THE LIGHT OF THE DECENTRALIZATION OF GOVERNANCE - Omelchak K.О. (Pressing Problems of Public Administration, 2017)
The results of implementation of the reform of decentralization of power in Ukraine are analyzed and the role of government regulation of land market in this process is determined. The assesses to the completeness and comprehensiveness of resource provision implementation of the reform of decentralization of power is identi ed.